Separation and purification technologies in biorefineries - Ramaswamy, Shri, 1957- (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2013)
Separation and purification processes play a critical role in biorefineries and their optimal selection, design and operation to maximise product yields and improve overall process efficiency. Separations and purifications are necessary for upstream processes as well as in maximising and improving product recovery in downstream processes. These processes account for a significant fraction of the total capital and operating costs and also are highly energy intensive. Consequently, a better understanding of separation and purification processes, current and possible alternative and novel advance.
Cover; Title Page; Copyright; Contents; List of Contributors; Preface; Part I Introduction; Chapter 1 Overview of Biomass Conversion Processes and Separation and Purification Technologies in Biorefineries; 1.1 Introduction; 1.2 Biochemical conversion biorefineries; 1.3 Thermo-chemical and other chemical conversion biorefineries; 1.3.1 Thermo-chemical conversion biorefineries; 1.3.1.1 Example: Biomass to gasoline process; 1.3.2 Other chemical conversion biorefineries; 1.3.2.1 Levulinic acid; 1.3.2.2 Glycerol; 1.3.2.3 Sorbitol; 1.3.2.4 Xylitol/Arabinitol.
Includes index.
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
Keywords: Biomass conversion; Biomass energy; Biomassa; Energia de la biomassa; NATURE -- Animals -- Wildlife; SCIENCE -- Life Sciences -- Biological Diversity; Biomass conversion; Biomass energy; Llibres electrònics; Electronic books